1991
DOI: 10.1037/0012-1649.27.1.159
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational transmission of harsh parenting.

Abstract: A social learning model was developed that portrayed four processes whereby harsh parenting might be transmitted across generations. The model was tested using a sample of 451 2-parent families, each of which included a 7th grader. Both parent self-report and adolescent-report measures were utilized for the harsh parenting construct. Analysis using structural equation modeling procedures showed that grandparents who had engaged in aggressive parenting produced presentday parents who were likely to use similar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
255
4
17

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 333 publications
(290 citation statements)
references
References 37 publications
14
255
4
17
Order By: Relevance
“…For example, low SES parenting is associated with higher levels of harsh punishment of their children (Simons et al, 1991) and lower levels of parental involvement (Luster et al, 1989). Specifically, in the Value of Children Study, Hoffman et al (1987) found that in families where the parents worked in a low SES job (e.g., manual or service sectors), these parents had a higher likelihood of enforcing strict rules than parents who worked in professional or managerial jobs.…”
Section: Does Ses Moderate the Relationship Between Parental Socializmentioning
confidence: 99%
“…For example, low SES parenting is associated with higher levels of harsh punishment of their children (Simons et al, 1991) and lower levels of parental involvement (Luster et al, 1989). Specifically, in the Value of Children Study, Hoffman et al (1987) found that in families where the parents worked in a low SES job (e.g., manual or service sectors), these parents had a higher likelihood of enforcing strict rules than parents who worked in professional or managerial jobs.…”
Section: Does Ses Moderate the Relationship Between Parental Socializmentioning
confidence: 99%
“…O termo harsh parenting 8 , por exemplo, tem sido utilizado para descrever um tipo de exercício do papel parental que varia em um contínuo entre interações ásperas, com uso de estratégias coercitivas e punição corporal até o emprego sistemático e extremo de punição física e crueldade com as crianças. Como destacam Simons, Whitbeck, Conger e Chyi-In 8 , aspereza na interação e abuso parental representam importantes fatores de risco para o desenvolvimento das crianças, sendo associados, por exemplo, à delinqüência, ao consumo de drogas e a dificuldades de relacionamento social.…”
Section: Introductionunclassified
“…Como destacam Simons, Whitbeck, Conger e Chyi-In 8 , aspereza na interação e abuso parental representam importantes fatores de risco para o desenvolvimento das crianças, sendo associados, por exemplo, à delinqüência, ao consumo de drogas e a dificuldades de relacionamento social. Adicionalmente, deve-se mencionar que estudos têm indicado que a transmissão intergeracional é um dos mecanismos de propagação da aspereza de interação entre pais e filhos, incluindo aqui o abuso 8 .…”
Section: Introductionunclassified
“…Recentemente, um rico cabedal de conhecimentos empiricamente embasados tem-se acumulado sobre a transmissão entre gerações de práticas parentais abusivas (Kaufman & Zigler, 1989;Simons, Whitbeck, Conger, Chyi-In, 1991) ou punitivas (Muller, Hunter & Stollak, 1995) e de atitudes parentais de rejeição (Lundberg, Perris, Schlette & Adolfsson, 2000;Whitbeck e cols., 1992). Conquanto o estilo autoritário englobe algumas dessas práticas e atitudes já investigadas, ainda não há evidência da intergeracionalidade do autoritarismo, enquanto estilo parental.…”
unclassified